Effect of vaginal flora on clinical outcome of frozen embryo transfer - Ji, Li; Peng, Chen; Bao, Xueyun (Frontiers in Cellular and Infection Microbiology, 2022)
Objective Vaginal microbiota imbalance is a high risk factor for premature birth, and is closely related to female pelvic inflammation and sexually transmitted diseases. The effect of vaginal microbiota on the outcome of assisted reproductive technology is still unclear. In this study, the vaginal microbial composition and the pregnancy outcome of frozen embryo transfer (FET) was investigated. Methods From October 2020 to December 2021, 275 FET cycles were selected from the center of reproductive medicine in Affiliated Hospital of Nantong University. Vaginal secretions were collected on the day of endometrium transformation, and smears were Gram stained. According to the Nugent score they were divided into three groups, including normal group, mild dysbiosis group and sever dysbiosis group. The clinical outcomes of each group were compared. Results In 275 FET cycles, the embryo implantation rate, clinical pregnancy rate and ongoing pregnancy rate in the normal group (66.9%,84.3% and 83.1%) were significantly higher than those in the mild dysbiosis group (45.5%, 57.3% and 49.3%) and in sever dysbiosis group (29.6%, 34.2% and 27%). The difference was statistically significant (P<0.01). When compared the preclinical pregnancy loss rate and the miscarriage rate, the normal group (1.3% and 1.3%) was significantly lower than those in the mild dysbiosis group (20.4% and 14.0%) and the sever dysbiosis group (25.5% and 21.1%). The difference was statistically significant (P<0.01), but there was no significant difference between the mild dysbiosis group and sever dysbiosis group (P>0.05). Conclusion Nugent score is directly related to the clinical outcome of FET. The Lactobacilli-dominant vaginal flora was a favorable factor for the good clinical outcome of FET, while asymptomatic bacterial vaginosis had a negative correlation with the outcome of FET.